MBCL-16. EFFICACY OF CARBOPLATIN GIVEN CONCOMITANTLY WITH RADIATION AND ISOTRETINOIN AS A PRO-APOPTOTIC AGENT IN MAINTENANCE THERAPY IN HIGH-RISK MEDULLOBLASTOMA: A REPORT FROM THE CHILDREN'S ONCOLOGY GROUP. (4th December 2020) - Leary, Sarah; Packer, Roger; Jaju, Alok; Heier, Linda; Burger, Peter; Smith, Kyle; Michalski, Jeff; Li, Yimei; Billups, Catherine; Hwang, Eugene; Gajjar, Amar; Pollack, Ian; et al.
Abstract: BACKGROUND: Metastasis, residual disease, and diffuse anaplasia are high-risk features in medulloblastoma. METHODS: This was a randomized phase 3 study. Patients age 3–21 years with high-risk medulloblastoma received (+/-) daily carboplatin with 36Gy craniospinal radiation and weekly Vincristine followed by six cycles of maintenance chemotherapy with Cisplatin, Cyclophosphamide and Vincristine (+/) 12 cycles of isotretinoin during and following maintenance. The primary endpoint was event-free survival, with exact log-rank test to compare arms. Retrospective molecular analysis included DNA methylation and exome sequencing. RESULTS: Of 294 medulloblastoma patients enrolled, 261 were eligible by central review of radiology and pathology, median age 8.6 years (range 3.3–21.2), 70% male, 189 (72%) with metastatic disease, 58 (22%) with diffuse anaplasia, 14 (5%) with >1.5cm2 residual disease. The 5-year EFS and OS for all subjects was 63%+4 and 73%+3, respectively. Isotretinoin randomization was closed due to futility. 5-year EFS was 66 + 5 with carboplatin versus 59 + 5 without (p=0.11), with effect exclusively observed in Group 3 subtype: 73%+8 with carboplatin versus 54%+9 without (p<0.05). Overall survival differed by molecular subgroup (p=0.006): WNT 100%, SHH 54%+11, Group 3 74%+6, Group 4 77%+5 at 5 years. MYC amplification or isochromosome 17 were unfavorable in Group 3 (p=0.029). Chromosome 11 loss or chromosome 17 gain were favorable in group 4 (p<0.001). No survival difference was observed with TP53 mutation in SHH subtype in this high-risk cohort. CONCLUSIONS: Therapy intensification with carboplatin improved survival for high-risk group 3 medulloblastoma. These findings further support an integrated clinical and molecular risk stratification for medulloblastoma.